Role of using Canephron N in the prevention of Urolithiasis after Lithotrepsy - Norman L. Ravera, Clement M. Rowland (Open Journal of Physicians and Surgeons, 2024)
Canephron N is a herbal preparation that has come to be used for a new purposed, that of preventing urolithiasis. This condition of forming stones in the urinary tract may make patients have recurrent pain and complications and this is what urolithiasis is all about. There is stone recurrence among patients after they have been treated through lithotripsy, and therefore it is important to apply some preventive measures. Clinical studies suggest that Canephron N may help lower stone formation risk by promoting urinary outflow of the substances from which stones form and increasing urine volume. The preparation is a complex of the herbal under it was primary developed, which is a mixture of centaury, rosemary and lovage, which is supposed to have the anti-spasmodic, anti-inflammation effect. These actions can also reduce lower urinary tract irritative symptoms as well as improve renal function. Moreover, Canephron N has a favorable safety profile and is well tolerated by patients, which makes it suitable for maintenance treatment for a long time in patients with a history of urolithiasis. The administration of Canephron N along with lifestyle modifications after lithotripsy has the potential of reducing stone recurrence and improving the patient outcome.